Notes on geoplasticity - Pariseau, W. G. (Netherlands : CRC Press, 2020)
'This book is about geoplasticity, solid mechanics of rock, jointed rock and soil beyond the domain of a purely elastic deformation. It will be of interest to civil, geological and mining engineers, particularly those involved in reliable design of excavations and foundations beyond elasticity, especially in jointed rock'--
Includes bibliographical references and index.
Keywords: Soils -- Plastic properties; Geotechnical engineering; Rock mechanics